Fresh Phyllanthus emblica (Amla) Fruit Supplementation Enhances Milk Fatty Acid Profiles and the Antioxidant Capacities of Milk and Blood in Dairy Cows - Mekonnen Tilahun; Liansheng Zhao; Lingling Sun; Yifan Shen; Lu Ma; Todd R. Callaway; Jianchu Xu; Dengpan Bu (MDPI AG, 2022)
The objective of this study was to investigate the effect of a diet supplemented with fresh amla fruit as a natural feed additive on blood metabolic parameters, milk antioxidant capacity, and milk fatty acid (FA) proportions in lactating dairy cows. Eight ruminally cannulated mid-lactation dairy cows were used in a repeated crossover design. The first group of four cows received total mixed ration (TMR) feed without fresh amla fruit (control group). The remaining four cows sequentially supplemented fresh amla fruit (FAF) at three levels (200, 400, then 600 g/d) (treatment group) at 14-day intervals. In second period, control and treatment groups were exchanged. The first ten days were adjusted to diet adaptation for each sub-period, and the last four days for sampling milk and blood. A total of 514 metabolites were detected from FAF using UPLC-ESI-MS/MS. The five main metabolites in FAF were phenolic acids (22%), flavonoids (20%), lipids (20%), amino acids and derivatives (9%), and tannins (7%). Amla fruit supplementation reduced total saturated fatty acid and the omega-6/omega-3 ratio at 200 or 400 g/d FAF dose compared to controls. In addition, amla fruit increased unsaturated FA, such as C20:5 (Eicosapentaenoic acid, EPA) and C22:6 (docosahexaenoic acid, DHA), and branched-chain FA in a dose-dependent manner at 200 or 400 g/d compared to controls. In addition, amla fruit increased the antioxidant capacity biomarkers in the blood, such as superoxide dismutase (SOD) and albumin; this confirms that amla fruit is an excellent antioxidant, inhibiting reactive oxygen species' (ROS) metabolism, and can thereby protect cells from oxidative stress. Moreover, the most remarkable improvement of ferric reducing-antioxidant power (FRAP) and total antioxidant capacity (TAC) in milk was recorded at 400 g/d FAF doses compared to controls. Therefore, fresh amla fruit doses for lactating cows at 400 g/d on an as-fed basis can be used as an alternative additive feed in dairy cow diets to improve antioxidant capacity, protein efficiency, butter quality, and to produce more desirable milk fatty acid profiles for human consumption.